Consumer Acceptance and Perceived Sensory Characteristics of Commercial Vegan Mayonnaise - Juyoun Lee; Kyunghee Kim (Foods)
This study aims to investigate the sensory characteristics of commercially available vegan mayonnaise using the Check-All-That-Apply (CATA) methodology and to determine the acceptability factors influencing consumer purchase intention. Six mayonnaise samples were evaluated by 112 consumers: one conventional mayonnaise and five commercially available vegan mayonnaises (labeled OGM, VVM, EBM, VM, SM, and OVM). Except for fatty flavor, rancid odor, artificial flavor, mouthcoating, melting, and mouthfeel, 15 characteristics (yellowness, glossiness, slimness, thickness, smoothness, beany odor, lemon aroma, nutty flavor, sourness, saltiness, sweetness, savory flavor, off-flavor, goes well with vegetables, and spreads well on crackers) were significantly different among 6 samples (p < 0.001). Across all evaluation attributes, OGM and VM had the highest acceptance, with no significant differences between the two samples except for overall taste. The VM was the only vegan mayonnaise that produced results similar to those of OGM, which is regular mayonnaise. The results of the study suggest that vegan mayonnaise can be a substitute for regular mayonnaise. We hope that this research will provide data that can be used as a basis for developing vegan mayonnaise products that meet the needs of consumers and food companies.